1991
DOI: 10.1039/jm9910100867
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic frustration, spirals and short-range order in CrxFe1 –xVO4–I solid solutions

Abstract: The crystal and magnetic structures of Cr,Fe,-,VO,-l solid solutions with x=0.25, 0.50, and 0.75 have been investigated by neutron diffraction and magnetic susceptibility measurements. Site occupancy refinements and geometrical arguments show that there is a small degree of Cr3+/Fe3+ ordering between two inequivalent octahedral sites with increasing x, as Cr3+ preferentially occupies the site that can become more regular. Antiferromagnetic order is observed below the N6el temperature TN=21.8(5) and 17.9(2) K f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Earlier studies on FeVO 4 have often indicated the formation of CrVO 4 -type or α-MnMoO 4 -type in low-temperature synthesis, whereas wolframite or α-PbO 2 -type phases appear at high-temperature synthesis (Figure ). On the other hand, the transition from FeVO 4 - I to CrVO 4 -type orthorhombic phase (FeVO 4 - II ) on substitution of amounts (about 20%) of Cr 3+ in the FeVO 4 - I lattice was observed. , The authors have indicated a small decrease in the unit cell volume (≈1.7%) can transform the triclinic FeVO 4 to monoclinic α-MnMoO 4 -type (SG C 2/ m ) structure. However, similar solid solutions at lower concentration (<20%) retain the original triclinic structure of FeVO 4 - I . ,, …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Earlier studies on FeVO 4 have often indicated the formation of CrVO 4 -type or α-MnMoO 4 -type in low-temperature synthesis, whereas wolframite or α-PbO 2 -type phases appear at high-temperature synthesis (Figure ). On the other hand, the transition from FeVO 4 - I to CrVO 4 -type orthorhombic phase (FeVO 4 - II ) on substitution of amounts (about 20%) of Cr 3+ in the FeVO 4 - I lattice was observed. , The authors have indicated a small decrease in the unit cell volume (≈1.7%) can transform the triclinic FeVO 4 to monoclinic α-MnMoO 4 -type (SG C 2/ m ) structure. However, similar solid solutions at lower concentration (<20%) retain the original triclinic structure of FeVO 4 - I . ,, …”
Section: Resultsmentioning
confidence: 97%
“…There is an important list of AB O 4 compounds that crystallize in this structure, being the most representative the A WO 4 compounds. The crystal structure of the FeVO 4 polymorphs is shown in Figure . Besides, the structural changes in FeVO 4 by chemical substitution have also been investigated in order to understand its structural variation as well as to tune its physical and chemical properties. ,,, It has been observed that a small substitution of other cations transforms the triclinic FeVO 4 - I to the monoclinic (SG C 2/ m ) α-MnMoO 4 -type structure and it remains stable in a wider range of compositions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase X crystallizes in the monoclinic system and its endcentered (C) unit cell parameters are given in Table 4. The literature scan has shown that angular positions of diffraction reflection, their relative intensities and unit cell parameter of phase X are similar to these ones of Fe 1-x Cr x VO 4 solid solution phase, CrVO 4 -I and InVO 4 -I, which are isostructural with a-MnMoO 4 [13][14][15][16]. It permits advancing suggestion, that phase X belongs to a group of orthovanadates, MVO 4 , isostructural with a-MnMoO 4 .…”
Section: Resultsmentioning
confidence: 94%
“…The literature survey has shown as well that in the FeVO 4 -CrVO 4 system solid solution of general formula Fe 1-x Cr x VO 4, for 0.1 \ x \ 0.85, forms, which adopts aMnMoO 4 structure [13,14]. Thus, the structure of the Fe 1-x Cr x VO 4 phase differs essentially from the stable at ambient conditions structures of triclinic FeVO 4 -I and orthorhombic CrVO 4 -III.…”
Section: Introductionmentioning
confidence: 99%